The starlets : a novel - Kelly, Lee; Thorne, Jennifer, 1980- (Harper Muse, 2024)
The tension on the set of a big-budget epic turns dealy when two rival starlets discover that members of the crew are using the production as a front for something decidedly illegal and that they are willing to kill to keep their dealings under wraps. When the two women find themselves on the run, they are forced to figure out how tto work together in order to save the day, the film, and maybe even each other.